2003
DOI: 10.1084/jem.20021408
|View full text |Cite
|
Sign up to set email alerts
|

Host Prostaglandin E2-EP3 Signaling Regulates Tumor-Associated Angiogenesis and Tumor Growth

Abstract: Nonsteroidal antiinflammatories are known to suppress incidence and progression of malignancies including colorectal cancers. However, the precise mechanism of this action remains unknown. Using prostaglandin (PG) receptor knockout mice, we have evaluated a role of PGs in tumor-associated angiogenesis and tumor growth, and identified PG receptors involved. Sarcoma-180 cells implanted in wild-type (WT) mice formed a tumor with extensive angiogenesis, which was greatly suppressed by specific inhibitors for cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
224
1
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 308 publications
(242 citation statements)
references
References 50 publications
11
224
1
6
Order By: Relevance
“…This difference could be explained by the existence of multiple receptors on cell surfaces for PGE 2 , which could compensate or act instead of the EP2 receptor. In this context, it has been shown that human umbilical vein endothelial cells express both EP2 and EP4 (Dormond et al, 2002), and EP3-null mice show decreased tumor growth and angiogenesis (Amano et al, 2003). Moreover, deletion of EP1 and EP4 inhibits tumor development (Watanabe et al, 1999;Mutoh et al, 2002), clearly suggesting that different EP receptors may mediate specific aspects of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be explained by the existence of multiple receptors on cell surfaces for PGE 2 , which could compensate or act instead of the EP2 receptor. In this context, it has been shown that human umbilical vein endothelial cells express both EP2 and EP4 (Dormond et al, 2002), and EP3-null mice show decreased tumor growth and angiogenesis (Amano et al, 2003). Moreover, deletion of EP1 and EP4 inhibits tumor development (Watanabe et al, 1999;Mutoh et al, 2002), clearly suggesting that different EP receptors may mediate specific aspects of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, little is known about the direct contribution of COX-2 to lymphedema-associated lymphangiogenesis, although positive correlations between COX-2 expression in tumor tissues and lymphangiogenesis and lymph node metastasis have been reported for several human cancers, [28][29][30] as well as the effect of COX-2 inhibition on lymphangiogenesis in a tumor implantation model. 14 In a study utilizing a nonselective COX inhibitor in a mouse tail lymphedema model, ketoprofen treatment normalized the histopathology with increased TNF-a expression and VEGF-C expression.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In both inflammatory and tumor models, an inducible cyclooxygenase-2 (COX-2)-derived PGE 2 exerted proangiogenic activity via EP3 signaling, with the concomitant induction of VEGF-A. This effect was especially prominent in bone marrow (BM)-derived cells, which are a major component of tumor stromal tissues.…”
mentioning
confidence: 99%
“…To this end, we used two selective EP 3 R antagonists L-798,106 [19] and ONO-AE 3 -240 [20]. As shown in Figure 4C and D, both EP 3 R antagonists (L-798,106 at 10 μM and ONO-AE 3 -240 at 10 nM) abolished the imetitinduced attenuation of NE exocytosis in cardiac synaptosomes.…”
Section: Increased Pge 2 Production Is Involved In the H 3 R-induced mentioning
confidence: 99%